Hospital survival upon discharge of ill-neonates transported by ground or air ambulance to a tertiary center - Jorge Luis Alvarado-Socarras; Alvaro Javier Idrovo; Anderson Bermon (Elsevier, 2016)
Objective: To evaluate the differences in hospital survival between modes of transport to a tertiary center in Colombia for critically ill neonates. Methods: Observational study of seriously ill neonates transported via air or ground, who required medical care at a center providing highly complex services. Data on sociodemographic, clinical, the Transport Risk Index of Physiologic Stability (TRIPS), and mode of transport were collected. Patients were described, followed by a bivariate analysis with condition (live or dead) at time of discharge as the dependent variable. A multiple Poisson regression with robust variance model was used to adjust associations. Results: A total of 176 neonates were transported by ambulance (10.22% by air) over six months. The transport distances were longer by air (median: 237.5 km) than by ground (median: 11.3 km). Mortality was higher among neonates transported by air (33.33%) than by ground (7.79%). No differences in survival were found between the two groups when adjusted by the multiple model. An interaction between mode of transport and distance was observed. Live hospital discharge was found to be associated with clinical severity upon admittance, birth weight, hemorrhaging during the third trimester, and serum potassium levels when admitted. Conclusions: Mode of transport was not associated with the outcome. In Colombia, access to medical services through air transport is a good option for neonates in critical condition. Further studies would determine the optimum distance (time of transportation) to obtain good clinical outcomes according type of ambulance. Resumo: Objetivo: Avaliar as diferenças na sobrevida hospitalar entre os modos de transporte para um centro terciário na Colômbia para neonatos gravemente doentes. Métodos: Estudo observacional de neonatos gravemente doentes transportados por ar ou terra que precisam de cuidados médicos em um centro que oferece serviços altamente complexos. Foram coletados dados sociodemográficos, clínicos, sobre o Índice de Risco da Estabilidade Fisiológica no Transporte (TRIPS) e o meio de transporte. Os pacientes foram descritos e submetidos a uma análise bivariada, com a condição (vivo ou morto) no momento da alta sendo a variável dependente. Uma regressão múltipla de Poisson com modelo de variância robusta foi utilizada para ajustar as associações. Resultados: Um total de 176 neonatos foram transportados por ambulância (10,22% pelo ar) ao longo de seis meses. As distâncias foram maiores pelo ar (mediana: 237,5 km) que por terra (mediana: 11,3 km). A mortalidade foi mais alta entre neonatos transportados pelo ar (33,33%) que por terra (7,79%). Não foram encontradas diferenças na sobrevida entre os dois grupos após o ajuste com o modelo múltiplo. Foi observada uma interação entre o meio de transporte e a distância. A alta hospitalar com vida foi associada à gravidade clínica na internação, ao peso ao nascer, à hemorragia durante o terceiro trimestre e aos níveis de potássio sérico na internação. Conclusões: O meio de transporte não foi associado ao resultado. Na Colômbia, o acesso a serviços médicos por transporte aéreo é uma boa opção para neonatos em condições críticas. Estudos adicionais determinariam a distância ideal (tempo de transporte) para obter bons resultados clínicos de acordo com o tipo de ambulância. Keywords: Ambulance, Ground, Air, Transport, TRIPS, Palavras-chave: Ambulância, Terrestre, Aérea, Transporte, TRIPS